2008
DOI: 10.1002/cncr.23572
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethnicity on the presentation and prognosis of patients with gastric adenocarcinoma

Abstract: BACKGROUND.Regional‐based studies have indicated that ethnicity is associated with presentation and outcome in patients with gastric adenocarcinoma. To validate this observation in a large cohort, the authors of this report used the National Cancer Data Base (NCDB) to determine whether self‐reported ethnicity influences presentation and survival in this patient population.METHODS.Patient demographics, tumor‐related features, and treatment‐related features were analyzed by ethnicity. Univariate analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
67
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 32 publications
7
67
2
Order By: Relevance
“…The incidences of different subtypes of gastric cancers (intestinal type vs. diffuse type, non-cardiac location vs. cardiac/gastroesophageal junctional location) differ between Asian and non-Asian populations. These different subtypes of gastric cancers are associated with different risk factors, clinical presentation, and treatment outcomes [14][15][16][17]. Therefore, clinical trials conducted in different regions of the world may enroll patients with heterogeneous biological backgrounds that make the trial results not comparable.…”
Section: Introductionmentioning
confidence: 99%
“…The incidences of different subtypes of gastric cancers (intestinal type vs. diffuse type, non-cardiac location vs. cardiac/gastroesophageal junctional location) differ between Asian and non-Asian populations. These different subtypes of gastric cancers are associated with different risk factors, clinical presentation, and treatment outcomes [14][15][16][17]. Therefore, clinical trials conducted in different regions of the world may enroll patients with heterogeneous biological backgrounds that make the trial results not comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have examined ethnicityrelated differences in survival after gastrectomy, showing prognoses to be superior for Asian and Hispanic patients over their Caucasian and African-American counterparts (17)(18)(19)(20)(21)(22)(23). This trend has been attributed to differences in patterns of disease presentation (i.e., proximal versus distal tumor location), and cultural differences in life style and social habits (17)(18)(19)(20)(21)(22). Interestingly, 2 studies found that patterns of tumor localization among Asians were more similar to the patterns among African Americans than among Caucasians (20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] We also demonstrated that race has an impact on patterns of disease presentation and survival rates in the United States. 8 For example, African Americans and Hispanics were more likely than other races to present with AJCC stage III or IV disease and to receive no adjuvant therapy. Although advanced stage at presentation is not an unusual feature of gastric cancer in the West, these findings also suggest that ethnicity may influence whether a patient receives adequate treatment for gastric adenocarcinoma.…”
mentioning
confidence: 95%